Multilingual - NFN Nurmiah (Multilingual, 2015)
The study aimed at describing the forms of code switching in thetransaction at traditional market of Manonda in Palu. Data wereanalyzed by employing descriptive method. The data of the study werethe utterances of buyers and sellers in the transaction. The data sourcesof the study were buyers and sellers who conducted the transaction attraditional market of Manonda in Palu. Data were collected byobservation, recording, and note-taking method. The result of the studyrevealed that the transaction at the traditional market of Manonda inPalu conducted by the buyers and sellers contained code switching. Theforms of code switching were Indonesian language to Bugineselanguage and vice versa, Indonesian language to Kaili language andvice versa, Indonesian language to Melayu Manado, and Indonesianlanguage to Javanese language and vice versa.